Fifty seven songs: for voice and piano - Strauss, Richard. 1864-1949 (Dover opera and choral scores, 1993)
This volume contains 57 of his finest songs, their sttings ranging from simple ("Morgen!") to ornate ("Allerseelen"), and their mood from serene ("Ruhe meine Seele") to passionate ("Sehnsucht).